Three Rooms ... - Stanton, Polly (RMIT University, 2024)
BACKGROUND Three Rooms is a work that is positioned within the field of acoustic ecology that depicts edge lands – isolated rural settings. This community of practice presents a survey of places situated outside mainstream society. Rarely do these works incorporate visuals aesthetics or aspire to artistic innovation through the specific use of technology. One exception is the sound work ‘Absent Presence’ (Philip Samartzis, 2016), which uses an array of specialist omni directional microphones and still images to capture Katabatic wind in Antarctica. Inspired by Samartzis’s work, Three Rooms utilizes specialist sound recording technology and includes the visual medium of video to render a multidimensional audio-visual experience of Iceland’s rarely heard or seen edge lands. CONTRIBUTION Three Rooms is a 10-minute video and multichannel sound installation that explores the interior remnants of an abandoned farmhouse in Iceland's remote Westfjords region. The work expands the field of acoustic ecology by ...